Answer:
![f(x) = (1-e^{-(1)/(2)x})[-e^(-x) +e^0]=(1-e^{-(x)/(2)})[1-e^(-x)]](https://img.qammunity.org/2021/formulas/mathematics/college/geecifn5bho94ydtqsvjxe1howtyi89ghv.png)
Explanation:
If we have two random variables Y1 and Y2 and we have th following limits:
![a_1 \leq Y_1 \leq a_2 , b_1 \leq Y_2 \leq b_2](https://img.qammunity.org/2021/formulas/mathematics/college/h6xlyo0wixsbehxug09zzalil3zde4zr8u.png)
We an find the density function with this formula:
![P(a_1 \leq Y_1 \leq a_2 ,b_1 \leq Y_2 \leq b_2)= \int_(b_1)^(b_2) \int_(a_1)^(a_2) f(y_1, y_2) dy_1 dy_2](https://img.qammunity.org/2021/formulas/mathematics/college/n0potgf4qhltc7qq4cd4ut2x7dnpbw54h9.png)
Now for our problem we know that for the two times of failure the density function is given by:
![f(t) = e^(-t) t>0](https://img.qammunity.org/2021/formulas/mathematics/college/9x6ruox73itkvgll3vq5v121ey7gfu7ff5.png)
And we know that the joint density for T1 and T2 is given by:
![f(t_1, t_2) =e^(-t_1)e^(-t_2), t_1 >0, t_2 >0](https://img.qammunity.org/2021/formulas/mathematics/college/59b0vrwqb3l6rv0jaiyl4ouxhwy6mrcwh7.png)
And we know that
![X= 2T_1 +T_2](https://img.qammunity.org/2021/formulas/mathematics/college/k8k52284cspfk1axckca68e59blajwlndi.png)
If we solve for
![T_1[/tex we got:</p><p>[tex] T_1 =(X-T_2)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/itag2e7hglx4d45jafcsd8bty5ypqkqxst.png)
And then we can find the density function like this:
![P(X \leq x) = P(2T_1 +T_2 \leq x)](https://img.qammunity.org/2021/formulas/mathematics/college/fhn2sm7ssmulmw27c77n2ckfysuorwxv14.png)
![\int_(0)^x \int_(0)^{(1)/(2)(x-t_2)} e^(-t_1)e^(-t_2) dt_1 dt_2](https://img.qammunity.org/2021/formulas/mathematics/college/6ehpygvasw0o48x0r0rubi9nnlpjz5lox8.png)
![=\int_(0)^x e^(-t_2) \int_(0)^{(1)/(2)(x-t_2)}e^(-t_1)dt_1 dt_2](https://img.qammunity.org/2021/formulas/mathematics/college/9ix8eu57nkltufd7jd4pwppoyqkfj3kiq1.png)
![=\int_(0)^x e^(-t_2) [-e^(-t_1) \Big|_0^{(1)/(2)(x-t_2)}] dt_2](https://img.qammunity.org/2021/formulas/mathematics/college/9mvxhjg33toiju30tfgc973zr65kzo7b5f.png)
![=\int_(0)^x e^(-t_2) [1-e^{-(1)/(2) (x-t_2)}] dt_2](https://img.qammunity.org/2021/formulas/mathematics/college/959ujaonvs33nze8swa6oj89kydegtpfw1.png)
![= \int_(0)^x (1- e^{-(1)/(2)x}) e^(-t_2)dt_2](https://img.qammunity.org/2021/formulas/mathematics/college/p29ctbk1k6x9cuzxv6ua3n12cwrl9ujz8d.png)
![= -(1-e^{-(1)/(2)x}) e^(-t_2) \Big|_0^x](https://img.qammunity.org/2021/formulas/mathematics/college/zyyegxqktxaoiyi8v3zrx1y8pqkoapt3hv.png)
![f(x) = (1-e^{-(1)/(2)x})[-e^(-x) +e^0]=(1-e^{-(x)/(2)})[1-e^(-x)]](https://img.qammunity.org/2021/formulas/mathematics/college/geecifn5bho94ydtqsvjxe1howtyi89ghv.png)